Learning curve analysis of robotic transabdominal preperitoneal inguinal hernia repair. Issue 6 (8th September 2020) - Aghayeva, Afag; Aytac, Erman; Dinc, Taha; Mutlu, Arda Ulas; Sahin, Inci; Bilgin, Ismail Ahmet; Hamzaoglu, Ismail; Baca, Bilgi
Abstract: Background: The purpose of this study was to assess the learning curve (LC) for inguinal hernia repair with robotic transabdominal preperitoneal (R‐TAPP) approach. Methods: Between April 2016 and October 2019, patients who underwent R‐TAPP were retrieved. Patient demographics, operative variables and postoperative outcomes were assessed. The moving average method and cumulative sum of operation times (OT) were used to evaluate the LC. The surgeon (BB) in this study had completed his laparoscopic (Lap) TAPP experience. Results: There were 50 (two females) consecutive patients (mean age was 51.7 ± 16.9 years). The first phase (learning phase) included initial 35 operations. The second phase included the next 15 operations. It was observed that, with increasing experience, a statistically significant shortening in the average OT by about 25 min was achieved ( p = 0.041). Conclusion: The LC phase for R‐TAPP, for surgeon with previous experience in Lap TAPP, seems to be very quick without compromising the operative morbidity.